KEWENANGAN MAHKAMAH SYAR’IYAH DI ACEH DIHUBUNGKAN DENGAN SISTEM PERADILAN DI INDONESIA - Efa Laela Fakhriah; Yusrizal ' (Fakultas Hukum Universitas Riau, 2013)
Islamic law in Aceh justice by theSyar'iyah Court a Special Courtwithin the Religious Courts. Islamiclaw in Aceh Judicial (Syar'iyahCourt) is a special court in thereligious courts throughout thejudicial authority concerningreligious authority, and a specialcourt in the general judicialauthority concerning all judicialauthority generally. CourtSyar'iyah authority as specialcourts as described in Section 3A ofAct Number 3 of 2006 is no longerlimited in the field of civil, but alsoincludes field mu'amalah andjinayah. As part of the Indonesianjudicial system, the Court Syar'iyahhas two basic competence, which isauthorized and partly ReligiousCourt authorized the General Court.Improvement regarding theadditional powers of the CourtSyar'iyah shall be in the form ofspecific legislation governingSyar'iyah Court as a special courtas stipulated in Article 24paragraph (3) of the 1945Constitution.